Karakteristik dan Faktor yang Berhubungan dengan Produksi ASI Ibu Nifas: Preliminary Study di Puskesmas Kota Semarang - Sri Rahayu; Suharyo Hadisaputro; Syarief Taufik Hidayat; Anggorowati (EMBRIO: Jurnal Kebidanan, 2022)
Approximately 38-63% of primiparous postpartum mothers experience lactation insufficiency, which has an impact on not breastfeeding their babies. The purpose of this study was to determine the characteristics and factors associated with postpartum mothers' milk production at the Public Health Center of Semarang City. This type of research is observational and cross-sectional design. The population of all postpartum women in Semarang City in October 2021, was taken by cluster random sampling at 8 selected health centers and a sample of 124 postpartum women. Methods of collecting data were questionnaires and data analysis with chi-square. The results of the research are the characteristics of mothers with an average age of 28 years, 56.5% of secondary education, 40% of primiparous parity, 59% of normal BMI, 92.7% of normal LILA, average age of the baby was 7 days, 82.3% of moderate anxiety level, 99.2% off good staff support, 58.9% of good surveillance worker support, 91.1% of good family support, 82.3% of more calorie intake of 2200 kcal, 62.1% of 1600 ml more fluid intake. There was a relationship between anxiety, family support, health volunteer support, calorie and fluid intake with breast milk production (p-value <0.05). There was no relationship between the support of health workers with postpartum mothers' milk production (p = 0.166). Mother’s psychological condition while breastfeeding, support from family, and health insurance are important things in increasing breast milk production as a continuation of breastfeeding and exclusive breastfeeding. In addition, calorie and fluid intake need to be considered to maintain the adequacy of mother's milk.